PENINGKATAN HASIL BELAJAR DAN MOTIVASI MELALUI PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN MULTIMEDIA PADA MATERI JUJUR, AMANAH, DAN ISTIQAMAH - Hanri Eko Saputro (IAIN Padangsidimpuan, 2015)
Abstract: Islamic education learning outcomes and optimal character will be the main capital in everyday life. On the other hand the presentation of learning Islamic education and Budi Character assessed tend to be indoktrinatif and not significantly so that the learning is very low. This is evident from the results of the average value of the ability of knowledge of students in the material honest, trustful, Istiqamah only 72.31, completeness percentage of 37.5%, from the observations of the percentage of students who are actively involved in the learning of only 40.63%. This study aims to improve learning outcomes and motivation of students in the material by using multimedia-aided model of Discovery Learning. Of the two cycles are performed in this study showed that the average ability of knowledge of learners into 78.78 in the first cycle and increased again to 84.91 in the second cycle. While the percentage of completeness of learners increased to 68.75% in the first cycle and increased again to 87.5% in the second cycle. Percentage of active participation of students also increased to 46.86% in the first cycle and increased to 84.38% in the second cycle. Keywords : Learning Outcomes, Motivations, Discovery Learning, MultimediaAbstrak: Hasil belajar pendidikan agama Islam dan mengoptimalkan pendidikan karakter akan menjadi modal utama dalam kehidupan sehari-hari. Pada sisi lain presentasi pembelajaran pendidikan Agama Islam karakter Budi Pekerti dinilai cenderung indoktrinatif dan tidak signifikan, sehingga pembelajaran sangat rendah. Hal ini terbukti dari hasil nilai rata-rata kemampuan pengetahuan siswa dalam penyelesaian materi tentang jujur, amanah, dan istiqamah memperoleh 72.31, persentase kelengkapan 37.5 %, dari pengamatan persentase siswa yang terlibat secara aktif dalam pembelajaran hanya 40, 63%. Model penelitian ini bertujuan untuk meningkatkan hasil belajar dan motivasi siswa dalam materi jujur, amanah, dan istiqamah dengan menggunakan multimedia dibantu dengan discovery learning. Dari dua siklus yang dilakukan dalam penelitian ini menunjukkan bahwa kemampuan rata-rata pengetahuan peserta didik menjadi 78.78 pada siklus I (pertama) dan meningkat lagi menjadi 84.91 pada siklus II (kedua). Sementara persentase kelengkapan peserta didik meningkat menjadi 68.75% pada siklus I dan meningkat lagi menjadi 87.5 pada siklus II. Kata Kunci: Hasil belajar, motivasi, discovery learning, multimedia.